Dvādaśa stotra of Śrī Madhvācārya - Madhva, 13th cent (Dharmaprakash Publications, 1975)
Hymns, in twelve cantos, eulogizing Krishna, Hindu deity and expounding the doctrine of devotion according to the dualistic (Dvaita) Vedanta tradition.